Evaluation of The Implementation of Occupational Safety and Health Management System (SMK3) in The Krueng Keureto DAM Construction Project, North Aceh - Sudirman; Richard Mareno; Kumita; Royanna Sakura; Maysa Fitri; Cut Azizah (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
The Occupational Safety and Health Management System (SMK3) is an integral part of the labor protection system. In construction services, it serves to minimize and prevent moral and material losses, loss of working hours, as well as risks to human safety and the surrounding environment, thereby supporting effective and efficient performance during the construction process. This study evaluates the implementation of SMK3 in the Krueng Keureuto Dam Construction Project in North Aceh Regency. A quantitative research approach was applied, with data collected from 30 respondents comprising the project manager, construction manager, safety officers, technical administration staff, document controllers, public relations officers, quality control staff, site engineers, field supervisors, logistics staff, warehouse staff, and project controllers. The research variables include the implementation of occupational safety and health, occupational safety and health regulations and procedures, management commitment to safety, work environment, and evaluation of occupational safety and health practices. The results show that the implementation of SMK3 in the Krueng Keureuto Dam Construction Project achieved a score of 94.22%, which falls into category 3, indicating a satisfactory level of performance